A Case Report on Chylolymphaticus Variety of Mesenteric Cyst - Sharmin, Shahanaj; Alam, Didarul; Rahman, Md Moklesur; Nargis, Seheli (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Mesenteric cyst is rare with a variable clinical presentation. The clinical presentation is not characteristic and the preoperative imaging although suggestive but not diagnostic. In most cases, the diagnosis is confirmed following surgical exploration. We report a case of chylolymphaticus variety of mesenteric cyst in18-year-old girl, who was presented to us with diffuse abdominal pain and lump in the lower abdomen for 14 days. Ultrasonography (USG) of the abdomen revealed large cystic lesion(12x10.8x11.4cm, volume77cc) in the abdominal cavity containing dense echogenic debris within, with no obvious flow in the wall-suggestive of twisted chocolate cyst. Exploration of the abdomen revealed a solitary cyst containing milky fluid about 55 cm distal to dudenojejunal flexure and twisted cyanosed coils of intestine. Histopathology of the excised cyst was consistent with chylolymphaticus cyst (Mesenteric cyst) J Bangladesh Coll Phys Surg 2019; 37(2): 83-85